Huge lipoma of tongue - Sanjog Chandak; P K Pandilwar; Tushar Chandak; Rupali Mundhada (Wolters Kluwer Medknow Publications, 2012)
Lipoma is the commonest benign tumor occurring at any anatomical site, where fat is present. In oral cavity and oropharynx, it is a relatively uncommon neoplasm. Tongue, which is totally devoid of fat cell is also a site for lipoma but very rarely. We report one such rare case of the universal tumor, of 20 years of duration and 9 cm in size, presenting at the lateral margin, dorsal and ventral surface of the tongue, for which complete tumor excision was done.